Readiness of Prospective Teachers for Imbibing Concepts of Happiness in their Pedagogy in the Era of Education 4.0 - vandana, Ms. (International Journal of Psychosocial Rehabilitation, 2020)
Education is dynamic concept and pedagogy is its reflection and happiness is its consequence. The content and contexts in education and its pedagogy must fulfill the expectations of living a prosperous and happy life. Education 4.0 should imbibe contemporary social, emotional and physical development of child which could synchronize with the deeds of happiness resolutions. So the concepts and contexts of Happiness (socio-emotional well-being) are becoming the key feather and feature of Education 4.0. It is becoming a core part of curriculum of school education since last few years as unrest in students seemingly very high. As a result of which happiness curriculum has been launched in many countries. In India also Directorate of education schools of Delhi on 2 July, 2018 launched happiness curriculum.This concept and contexts of happiness is required to be taken by the teachers in the classroom. As a way it was imperative to incorporate these content and concepts of happiness in the present curriculum of Prospective Teachers of DIETs. Now these perspective teachers are getting training in the content and contexts of happiness curriculum. Their readiness in these happiness issues and how well they are acquainting with it becomes a matter of interest of this research paper. This paper tries to reveal the present state of mind of these prospective teachers. For this study, the sample of 50 trainees was taken from DIET Pitampura, Delhi. Focussed group discussion and self-developed questionnaire were administered on the sample by researcher. The data gathered was analysed using suitable statistical/non statistical techniques. The realistic point of view of Prospective Teachers was come up regarding their readiness of concept and concepts of Happiness in their pedagogy in schools.